Enhancement of Interfacial Wettability between Al-Zn Alloy Matrix and MnO2 Decorated with Ni for Effective Cathodic Protection Systems - Jacob, Sunil; Binoj, K.K.; Benny, Dona; Jinu, P.Y. (Asian Journal of Chemistry, 2023)
Substrates made of steel used in coastal applications are regularly exposed to harsh salty environments; as a result, it is essential to adopt reliable strategies for preventing corrosion. Utilization of aluminum rich sacrificial anodes is an efficient anticorrosive technique owing to its high columbic amplitude, low density, inherent negative potential and galvanic economy. In this work, the electrochemical and micro-structural was characterized by catalytic effect of MnO2-Ni on anode activation. MnO2-Ni present in anode matrix results in destroyed passive alumina film and facilitates the galvanic growth on an anode. The anode exhibited active operating potential and high columbic efficiency during prolonged marine exposure studies. High anodic efficacy was performed by fine tuning composites into the metal matrix Al based alloy. The results revealed that the preferential dissolution of intermetallic particles induced effective sacrificial anode action.